2023
DOI: 10.3389/fnins.2023.1180829
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological model of human temporal contrast sensitivity based on SSVEP

Tsvetomira Tsoneva,
Gary Garcia-Molina,
Peter Desain

Abstract: The present study aims to connect the psychophysical research on the human visual perception of flicker with the neurophysiological research on steady-state visual evoked potentials (SSVEPs) in the context of their application needs and current technological developments. In four experiments, we investigated whether a temporal contrast sensitivity model could be established based on the electrophysiological responses to repetitive visual stimulation and, if so, how this model compares to the psychophysical mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 68 publications
(140 reference statements)
1
5
0
Order By: Relevance
“…It is also important to consider that the success of eliciting SSVEP responses using light stimulation of extremely low contrast and intensity may be, at least partly, related to the surface covered by the flickers. Indeed, it can be argued that the flickers implemented in the present study, but also in previous studies reporting SSVEP responses elicited by imperceptible flickers (Lingelbach et al, 2021; Tsoneva et al, 2023), were rather large. Indeed previous research has shown that flicker size is positively correlated with SSVEP response amplitude (Duszyk et al, 2014; Ng et al, 2012).…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…It is also important to consider that the success of eliciting SSVEP responses using light stimulation of extremely low contrast and intensity may be, at least partly, related to the surface covered by the flickers. Indeed, it can be argued that the flickers implemented in the present study, but also in previous studies reporting SSVEP responses elicited by imperceptible flickers (Lingelbach et al, 2021; Tsoneva et al, 2023), were rather large. Indeed previous research has shown that flicker size is positively correlated with SSVEP response amplitude (Duszyk et al, 2014; Ng et al, 2012).…”
Section: Discussionsupporting
confidence: 52%
“…This study aimed to assess the validity of minimally intrusive (periliminal) and imperceptible (subliminal) kering light stimulation as an approach to enhance frequency-tagging implementations. The present study builds upon previous research that had demonstrated the feasibility of recording SSVEP responses with imperceptible flickers (Tsoneva et al, 2023; Lingelbach et al, 2021). In the present study, the contrast and intensity of flickering visual stimulation were reduced down to the perceptual visibility threshold, reducing their intrusiveness.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations